The Impact of Open Innovation on Organizational Performance: Mediating Role of Social Capital in Small and Medium Enterprises in the Kingdom of Saudi Arabia - Alwehabie, Abdullah (Journal of Ecohumanism, 2024)
Over the past two decades, open innovation and its impact on the organizational performance of SMEs have been little discussed. The main objective of this research is to analyze the impact of open innovation on the economic and operational performance of SMEs working in a very important sector such as the oil sector. This research also tested the mediating role of social capital in the relationship between open innovation and the organizational performance of SMEs. The study used deductive reasoning by applying the quantitative method. The data were collected from 250 small and medium-sized enterprises working in the oil sector. Correlation analysis, regression analysis, and normal test theory were used as statistical tests with the help of PLS. The statistical results confirmed that all predictive elements significantly elucidate the consequence elements. The results of the mediation analysis also confirm that social capital plays a mediating role in the association between open innovation and organizational performance. This study enriches the available theory by evaluating the mediating role of social capital and the link between open innovation and organizational performance, thereby making a significant contribution to the dominant theory by contextualizing SMEs in the oil sector in Saudi Arabia, with an emphasis on the associations between open innovation, social capital, economic performance, and operational performance.